Relação entre tamanho e armazenamento de sementes de soja colhidas no cerrado de Roraima na qualidade física e fisiológica - Barbosa, Cylles Zara dos Reis (2009)
A single soybean cultivar may show diversity concerning to size of seeds. Variability in seed size may cause reduction both in physical quality and in physiological quality of seeds, besides may also present diversity of performance during storage. In this way, this study intended to estimate the relationship between size and storage of soybean seeds harvested in savannas of Roraima and their physical and physiological qualities. Seeds of two soybean cultivars, BRS Candeia and BRS Tracajá were grown as a commercial crop, from May to September of 2007, at Paraíso Farm, located in the municipality Bonfim, 116 km far from city of Boa Vista- RR. Seeds were cleaned and classified by size, utilizing three sieves with round holes of dimensions measuring 6.0, 6.5 and 7.0 mm for seeds of cultivar BRS Candeia and 5.5, 6.0 and 6.5 mm for seeds of cultivar BRS Tracajá and subsequently disposed in multifoliated paper bags and stored for a period of six months under controlled conditions of temperature (23ºC) and air relative humidity (60%), in Laboratory of Seed Analysis from Embrapa Roraima, in Boa Vista, Roraima. The experimental design was entirely randomized, in factorial scheme 3X4 (seed size x storage periods) with twelve replicates. Seed quality was assessed in beginning of storage and after two, four and six months of storage according to mass of a thousand seeds, electrical conductivity, seedling length, seedling dry mass, dry mass per seedling, seedling field emergence, speed of field seedling emergence, germination first counting and germination. The largest seeds of soybean cultivars, BRS Candeia and BRS Tracajá show the best physical and physiological quality during storage. The largest seeds of cultivars BRS Candeia (7.0 mm) and BRS Tracajá (6.5 mm) present the higher value for mass of a thousand seeds (greater than 24.1 g and 18.5 g, respectively). Soybean seeds speed of seedling field emergence decrease with smaller size and bigger storage period. The highest physiological quality of soybean seeds of both cultivars was observed within seeds of greater size which present higher germination in storage.